Impact of family-related factors on mental health and adjustment of adolescents (Indian Journal of Child Health, 2019)
Background: Adolescence is believed to be a period of great stress and storm, as rapid physical and mental changes occur during this period with a lot of problems in adjustment of children. Objective: The objective of this study was to assess the impact of family-related factors on mental health and adjustment in adolescents. Materials and Methods: This is a cross-sectional study involving 175 school-going boys and girls of age 14–17 years. The students were administered a sociodemographic pro forma, general health questionnaire-28 (GHQ-28), and adjustment inventory for school students (AISS) by one-to-one interview method. Family-related factors such as maternal education and occupation, relationship of the primary caregiver, type of family, and number of siblings were analyzed with the scores of GHQ and AISS by Student’s Mann–Whitney U-test and Kruskal–Wallis test using the SPSS 20.0. Results: Poorer maternal education is associated with greater anxiety and insomnia than those of mothers with better education (p=0.008), while maternal occupation had a negative impact on overall adjustment scores (p<0.0001). Children from nuclear family and children reared by grandparents showed significantly greater social dysfunction (p<0.0001). Emotional adjustment, educational adjustment, and overall adjustment scores were significantly higher in children from nuclear family. Significant increase in the educational adjustment scores is seen in children brought up by parents. Social dysfunction was more among students who had two siblings when compared to children with one sibling (p=0.01). Conclusion: Family-related factors significantly affect the mental health and coping nature of the adjustment-related problems.